UV and RP-HPLC Method for the Estimation of Lamivudine in Bulk and Pharmaceutical Dosage Forms - Mohanraj, P.; Gauthaman, K. (Asian Journal of Chemistry, 2010)
Two assay procedures based on UV-spectrophotometry and reversed phase high performance liquid chromatography (RP-HPLC) have been developed for the determination of lamivudine in bulk drug and pharmaceutical formulations. UV spectrophotometry involves the determination of lamivudine by dissolving it in methanol followed by measuring absorbance at 272 nm. The HPLC determination carried out on a Luna 5u C-18 column using a mobile phase consisting of methanol:water (89:11) at a flow rate of 1.0 mL/min with UV detection at 272. UV spectroscopic method is applicable over 2.5-20 μg/mL range of lamivudine with a molar absorptivity 1.155 × 103 L mol-1 cm-1 and a Sandell's sensitivity of 0.02265 μg/cm2. In HPLC method a rectilinear relationship was observed between 5-100 μg/mL and analysis time was 10 min. The retention time was found to be 2.7 min. The methods when apply to the determination of lamivudine in dosage form gave satisfactory results. The developed methods were found to be precise and accurate from the statistical validation of the analysis data.